GRATIFIKASI DALAM PERSPEKTIF MAHASISWA AKUNTANSI: DILEMA ATAU PROBLEMATIKA - Ersyafdi, Ilham Ramadhan; Ginting, Rafles (Faculty of Economics and Business University of Mataram, 2024)
The high desire of students to become civil servants and State-owned enterprises (SOEs) is a big task that needs to be prepared. One of them is how they view gratification as something that tends to become a culture and is considered normal because this work is related to service to the country. Therefore, this study aims to determine the description of accounting students' understanding of gratification based on logical and moral perspectives. This study uses mixed methods, namely a combination of quantitative and qualitative approaches. The instrument used was a questionnaire containing case examples of gratification, interviews, and previous studies. The study's results show that the majority of student respondents (65.31%) have not been able to interpret gratification correctly, even though the majority of 70% have taken ethics courses, but only a few have taken anti-corruption/investigative audit education courses. The government must require universities to provide anti-corruption education courses as mandatory subjects so that anti-corruption behavior and personality are formed so that they can prevent and eradicate gratification and corruption. It is hoped that this course can shape students' skills and enthusiasm as agents of change for a social life that is free from the threat of corruption. This study can also be used to expand knowledge and enrich the literature regarding student understanding of gratification.